Resin composition and molded article
By using the resin composition of methacrynal components and styrene resin, the problem of difficulty in the heat -resistant, surface hardness, and impact resistance of the existing thermoplastic resin to achieve excellent physical characteristics and surface appearance. , Applicable to automotive components.
Patent Information
- Application Number
- CN202380049105.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-11
- Filing Date
- 2023-05-10
- Publication Date
- 2025-01-21
AI Technical Summary
When the existing thermoplastic resin improves heat resistance, surface hardness and impact resistance, it is difficult to achieve a good balance, and there are surface appearance problems such as poor coloring and glossiness.
A resin composition containing methacrynal components and styrene resin uses the composition and proportions of the symbol to optimize the physical characteristics of the resin by adjusting the composition and proportion of the cluster. Specifically, methyl acrylic groups contain methyl acrocylite units, alpha-methacopyrene units, styrene units, and Malay acid anhydrials. The styrene resin contains ABS, AES, ASA, or AS resin.
The excellent heat resistance, surface hardness, impact resistance and surface appearance of the resin composition can be applied to the interior or external decoration components.
Smart Images

Figure CN119343403A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition comprising a methacrylic copolymer and a styrene resin, a molded article, and an automobile interior or exterior part comprising the molded article. Background Art
[0002] Conventionally, maleimide copolymers represented by N-phenylmaleimide-styrene copolymers have been used for the purpose of improving the heat resistance of thermoplastic resins such as acrylonitrile-butadiene-styrene (ABS) resin and acrylonitrile-styrene (AS) resin (Patent Documents 1 and 2).
[0003] However, although maleimide copolymers can improve the heat resistance and / or surface hardness of thermoplastic resins (such as ABS resins and AS resins), they deteriorate impact resistance, surface appearance (gloss and color tone), and other physical properties.
[0004] In order to solve these problems, Patent Document 3 discloses a maleimide copolymer in which an acrylonitrile monomer is copolymerized as a third monomer. In addition, Patent Document 4 discloses a maleimide copolymer in which a methacrylate monomer is copolymerized as a third monomer. Although copolymerization with an acrylonitrile monomer increases the entanglement density between molecules and improves impact resistance, there is a problem of strong coloration. In addition, although copolymerization with a methacrylate monomer imparts glossiness generated by the methacrylate monomer and suppresses coloration by reducing the amount of residual maleimide monomer, thereby improving the surface appearance, heat resistance is insufficient.
[0005] As described above, there is still room for research on technologies for improving the heat resistance of thermoplastic resins (such as ABS resin and AS resin) and achieving a further good balance among surface hardness, surface appearance, and impact resistance.
[0006] Citation List
[0007] Patent Literature
[0008] Patent Document 1: JPS57-98536A
[0009] Patent Document 2: JPS57-125241A
[0010] Patent Document 3: JPH03-205411A
[0011] Patent Document 4: JP2001-233919A Summary of the invention
[0012] Technical issues
[0013] In view of the above circumstances, an object of the present invention is to provide a resin composition having various excellent physical properties such as heat resistance, surface hardness, impact resistance and surface appearance.
[0014] Technical solutions to the problem
[0015] As a result of studies conducted to achieve the above-mentioned object, the present invention including the following embodiments has been completed. [1]
[0017] A resin composition comprising:
[0018] 5 to 49 parts by mass of a methacrylic copolymer (A), the methacrylic copolymer (A) comprising 5 to 97% by mass of methyl methacrylate units, 1 to 70% by mass of a structural unit (R) represented by the following formula (I), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one unit selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit;
[0019] 51 to 95 parts by mass of one or more styrene resins (B) selected from the group consisting of ABS resins, AES resins, ASA resins and AS resins; and
[0020] 0 to 30 parts by mass of a methacrylic resin (C),
[0021]
[0022] Wherein in formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 is a hydrogen atom, C1-C 18 Alkyl, C3-C 12 Cycloalkyl, or C6-C 15 Organic group. [2]
[0024] The resin composition according to [1], wherein in the methacrylic copolymer (A), the total content of α-methylstyrene units and styrene units is 2 to 40% by mass based on all structural units, and the proportion of α-methylstyrene units is 51 to 99% by mass based on the total content of α-methylstyrene units and styrene units. [3]
[0026] The resin composition according to [1] or [2], wherein in the methacrylic copolymer (A), the content of the structural unit (R) is 20 to 60% by mass based on all structural units. [4]
[0028] The resin composition according to any one of [1] to [3], wherein in the methacrylic copolymer (A), the formation reaction of the structural unit (R) is an imide cyclization reaction in which an imidizing agent is added to a precursor polymer in an extruder, and the resulting mixture is kneaded and reacted. [5]
[0030] The resin composition according to any one of [1] to [4], wherein the Vicat softening temperature of the resin composition measured by the method described in JIS K 7206 B50 method is 105° C. to 140° C. [6]
[0032] The resin composition according to any one of [1] to [5], wherein the styrene resin is an ASA resin. [7]
[0034] A molded article comprising the resin composition according to any one of [1] to [6]. [8]
[0036] An injection molded article comprising the resin composition according to any one of [1] to [6]. [9]
[0038] The molded article according to [7] or [8], which is used as an interior part or exterior part of an automobile.
[0039] Advantageous Effects of the Invention
[0040] According to the present invention, a methacrylic copolymer having excellent heat resistance, rigidity and fluidity, and excellent compatibility with a styrene resin is used, so that a molded body comprising a resin composition having excellent heat resistance, surface hardness, impact resistance, moldability and surface appearance, and an automotive interior or exterior part comprising the molded body can be obtained. DETAILED DESCRIPTION
[0041] In the present specification, singular forms (eg, "a," "an," and "the") are intended to include both the singular and the plural, unless otherwise indicated in the specification or clearly contradicted by context.
[0042] The resin composition of the present invention comprises a methacrylic copolymer (A) and a styrene resin (B). In the resin composition, the content of the methacrylic copolymer (A) is in the range of 5 to 49% by mass, preferably 10 to 45% by mass, and more preferably 15 to 40% by mass. In the resin composition of the present invention, when the content of the methacrylic copolymer (A) is 5% by mass or more, the resin composition has excellent heat resistance and surface hardness, and when the content of the methacrylic copolymer (A) is 49% by mass or less, the impact resistance can be maintained.
[0043] Methacrylic acid copolymer (A)
[0044] The methacrylic copolymer (A) according to the present invention comprises 5 to 97% by mass of methyl methacrylate units, 1 to 70% by mass of structural units (R), 1 to 48% by mass of α-methylstyrene units, 1 to 48% by mass of at least one unit selected from the group consisting of styrene units and maleic anhydride units, and 0 to 20% by mass of unsubstituted or N-substituted maleimide units. The methacrylic copolymer (A) used in the present invention may also include other vinyl monomer units that can be copolymerized with methyl methacrylate. In the present invention, the structural unit in the polymer refers to a repeating unit constituting the polymer or a unit obtained by derivatizing at least a portion of the repeating unit (e.g., an unsubstituted or N-substituted glutarimide unit). In this specification, the term "structural unit" can be used to collectively refer to methyl methacrylate units, structural units (R), α-methylstyrene units, styrene units or maleic anhydride units, unsubstituted or N-substituted maleimide units and other vinyl monomer units.
[0045] In the methacrylic copolymer (A) according to the present invention, the ratio of the methyl methacrylate unit is 5 to 97 mass %, preferably 6 to 95 mass %, more preferably 7 to 90 mass %, and further preferably 10 to 70 mass % based on all structural units. The ratio of the methyl methacrylate unit is preferably within the above range from the viewpoint of the total light transmittance and thermal decomposition resistance of the obtained methacrylic copolymer.
[0046] In the methacrylic copolymer (A) according to the present invention, the ratio of the α-methylstyrene unit is 1 to 48% by mass, preferably 3 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 7 to 30% by mass based on the total structural units. For example, from the viewpoints of heat resistance, elastic modulus, compatibility with styrene resins and thermal decomposition resistance of the resulting methacrylic copolymer, from the viewpoint of productivity (polymerizability), and further from the viewpoint of preventing inhibition of glutarimidization reaction caused by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid to be described below, the ratio of the α-methylstyrene unit is preferably within the above range.
[0047] In the methacrylic copolymer (A) according to the present invention, the ratio of the styrene unit and / or the maleic anhydride unit is 1 to 48% by mass, preferably 3 to 40% by mass, more preferably 5 to 35% by mass, and further preferably 7 to 30% by mass, based on all the structural units. For example, from the viewpoint of the heat decomposition resistance, fluidity and heat resistance of the obtained methacrylic copolymer, and further from the viewpoint of the inhibition of the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid to be described below, the ratio of the styrene unit is preferably within the above range. For example, from the viewpoint of the heat decomposition resistance and fluidity of the obtained methacrylic copolymer, and further from the viewpoint of the inhibition of the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid to be described below, the ratio of the maleic anhydride unit is preferably within the above range. In the present invention, it is preferred to contain a styrene unit having excellent compatibility with the styrene resin (B).
[0048] In the methacrylic copolymer (A) according to the present invention, the total ratio of α-methylstyrene units and styrene units is preferably 2 to 40 mass %, more preferably 5 to 35 mass %, and further more preferably 10 to 30 mass % based on all structural units. When the total ratio of α-methylstyrene units and styrene units is within the above range, the glutarimidization reaction caused by the intramolecular cyclization of two adjacent structural units derived from (meth) acrylic acid described below is less likely to be inhibited. In addition, based on the total ratio of α-methylstyrene units and styrene units, the ratio of α-methylstyrene units is preferably 30 to 95 mass %, more preferably 35 to 90 mass %, and further more preferably 40 to 85 mass %. When the ratio of α-methylstyrene units is within the above range, the methacrylic copolymer used in the present invention has high heat resistance and rigidity.
[0049] The structural unit (R) is a structural unit having one or more ring structures selected from the group consisting of N-substituted or unsubstituted glutarimide units in the main chain.
[0050] The N-substituted or unsubstituted glutarimide unit is a unit having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure. Examples of units having an N-substituted or unsubstituted 2,6-dioxopiperidinediyl structure include structural units represented by formula (I). The N-substituted glutarimide unit may be, for example, one or more units selected from N-methylglutarimide units, N-butylglutarimide units, N-cyclohexylglutarimide units, N-phenylglutarimide units, and the like.
[0051]
[0052] In formula (I), R 1 Each independently represents a hydrogen atom or a methyl group, preferably two R 1 All are methyl. 2 is a hydrogen atom, C1-C 18 Alkyl, C3-C 12 Cycloalkyl, or C6-C 15 The organic group is preferably a methyl group, a n-butyl group, a cyclohexyl group or a benzyl group, more preferably a methyl group, a n-butyl group or a cyclohexyl group, and most preferably a methyl group.
[0053] The structural unit (R) can be formed, for example, by an imide cyclization reaction, in which an imidizing agent is added to a precursor polymer in an extruder, and the resulting mixture is kneaded and reacted. In a preferred embodiment, the structural unit represented by formula (I) can be formed, for example, by reacting the corresponding acid anhydride (IIa) with a precursor polymer represented by R as shown in scheme (i). 2 It is preferably produced by reacting an imidizing agent represented by NH2, or by an intramolecular cyclization reaction of a copolymer having a partial structure of formula (III). It is preferably heated to convert the structural unit represented by formula (III) into the structural unit represented by formula (I) by an intramolecular cyclization reaction.
[0054] Solution (i)
[0055]
[0056] In the formula, R 1 and R 2 As defined above.
[0057] The N-substituted or unsubstituted glutarimide unit can be obtained by the method described in WO2005 / 10838A1, JP2010-254742A, JP2008-273140A, JP2008-274187A, etc., specifically, for example, by reacting two adjacent structural units derived from methyl (meth)acrylate or glutaric anhydride units with an imidizing agent, such as an amine containing an aliphatic hydrocarbon group (such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine or n-hexylamine); an amine containing an aromatic hydrocarbon group (such as aniline, toluidine, or trichloroaniline); an amine containing an alicyclic hydrocarbon group (such as cyclohexylamine); or urea, 1,3-dimethylurea, 1,3-diethylurea or 1,3-dipropylurea. Among them, methylamine is preferred. When the imidization reaction is performed, a part of the methyl methacrylate unit may be hydrolyzed to form a carboxyl group. The carboxyl group is preferably restored to the original methyl methacrylate unit by an esterification reaction performed by treatment with an esterifying agent. The esterifying agent is not particularly limited as long as it can provide the effect of the present invention. Preferred examples of the esterifying agent include dimethyl carbonate and trimethyl acetate. In addition to the esterifying agent, a tertiary amine such as trimethylamine, triethylamine or tributylamine may also be used together as a catalyst.
[0058] In the methacrylic copolymer (A) according to the present invention, the ratio of the structural unit (R) is 1 to 70% by mass, preferably 12 to 68% by mass, more preferably 15 to 65% by mass, and further preferably 20 to 60% by mass based on all structural units. In view of solving the problem of the present invention and considering that the increase in the content of the structural unit (R) will improve the heat resistance and thermal decomposition resistance of the methacrylic copolymer, the ratio of the structural unit (R) is preferably above the above lower limit. In addition, from the viewpoint of reducing melt viscosity and improving molding processability, it is preferably below the above upper limit.
[0059] The methacrylic copolymer (A) according to the present invention may or may not contain an N-substituted or unsubstituted maleimide unit in addition to the structural unit (R) and the like. Therefore, in the present invention, the expression "a methacrylic copolymer (A) containing 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit" may also include a methacrylic copolymer (A) not containing an unsubstituted or N-substituted maleimide unit. The N-substituted or unsubstituted maleimide unit is a unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure.
[0060] Examples of the unit having an N-substituted or unsubstituted 2,5-pyrrolidinedione structure include a structural unit represented by formula (VI).
[0061]
[0062] In formula (VI), R 10 is a hydrogen atom, C1-C 18 Alkyl, C3-C 12 Cycloalkyl or C6-C 15 Organic group.
[0063] The structural unit represented by formula (VI) can be obtained, for example, by polymerizing a monomer mixture containing the monomer represented by formula (VI), or by polymerizing a monomer mixture containing maleic anhydride to obtain a reaction product with a maleic anhydride unit represented by R 3 The methacrylic acid polymer is introduced into the methacrylic acid polymer by reacting with an imidizing agent represented by NH2.
[0064] The N-substituted or unsubstituted maleimide unit is obtained by the method described in JP61-026924A, JPH07-042332A, JPH09-100322A, JP2001-329021A, etc., specifically, by the reaction of maleic anhydride unit with an imidizing agent, the imidizing agent is, for example, an amine containing an aliphatic hydrocarbon group (such as ammonia, methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine or n-hexylamine); an amine containing an aromatic hydrocarbon group (such as aniline, toluidine, or trichloroaniline); an amine containing an alicyclic hydrocarbon group (such as cyclohexylamine); or urea, 1,3-dimethylurea, 1,3-diethylurea or 1,3-dipropylurea. Among them, methylamine is preferred.
[0065] In the methacrylic copolymer (A) according to the present invention, the ratio of the N-substituted or unsubstituted maleimide unit is 0 to 20% by mass, more preferably 0 to 15% by mass, and further more preferably 0 to 10% by mass based on all structural units.
[0066] The methacrylic copolymer (A) according to the present invention may contain another vinyl monomer unit copolymerizable with the methyl methacrylate unit. The other vinyl monomer unit can be appropriately selected according to the desired properties of the methacrylic copolymer (A). When properties such as thermal stability, fluidity, chemical resistance, optical properties and compatibility with other resins are particularly required, it is preferred to use at least one selected from an acrylate monomer unit, an aromatic vinyl monomer unit other than styrene and α-methylstyrene, and an acrylonitrile monomer unit.
[0067] Among the monomers constituting the above-mentioned monomer units, at least one selected from the group consisting of methyl acrylate, ethyl acrylate and acrylonitrile is preferred from the viewpoint of easy availability.
[0068] Examples of the additional vinyl monomer unit copolymerizable with methyl methacrylate also include a methacrylamide unit represented by the following formula (A) and a 2-(hydroxyalkyl)acrylate unit represented by the following formula (B).
[0069]
[0070] In the formula, R 3 is a hydrogen atom, C1-C 18 Alkyl, C3-C 12 Cycloalkyl or C6-C 15 An organic group, preferably a hydrogen atom, a methyl group, a n-butyl group, a cyclohexyl group or a benzyl group, more preferably a methyl group, a n-butyl group or a cyclohexyl group; R 4 and R 5 are independently a hydrogen atom or a C1-C 20 An organic group is preferably a hydrogen atom or a C1-C 10 The organic group is more preferably a hydrogen atom or a C1-C5 organic group. The organic group is not particularly limited as long as it contains 1 to 20 carbon atoms. Examples of the organic group include straight chain or branched chain alkyl, straight chain or branched chain aryl, -OCOCH3 and -CN. The organic group may contain heteroatoms, such as oxygen atoms. R 4 Preferably, methyl, R 5 Preferred is a hydrogen atom.
[0071] According to the methacrylic copolymer (A) of the present invention, in addition to the structural unit (R) and the like, a lactone ring unit may also be included as an additional vinyl monomer unit. The lactone ring unit is a structural unit containing a >CH-OC(=O)-group in the ring structure. In the structural unit containing a >CH-OC(=O)-group in the ring structure, the number of elements constituting the ring is preferably 4 to 8, more preferably 5 to 6, and most preferably 6. Examples of the structural unit containing a >CH-OC(=O)-group in the ring structure include lactone dibase structural units, such as β-propiolactone dibase structural units, γ-butyrolactone dibase structural units, and δ-valerolactone dibase structural units. The structural unit containing a >CH-OC(=O)-group in the ring structure can be obtained, for example, by intramolecular cyclization of a polymer having a hydroxyl group and an ester group using the hydroxyl group and the ester group. Wherein “>C” means that the carbon atom C has two bonding bonds.
[0072] Examples of the δ-valerolactone diyl structural unit include a structural unit represented by formula (IV).
[0073]
[0074] In formula (IV), R 6 , R 7and R 8 are independently a hydrogen atom or a C1-C 20 An organic group is preferably a hydrogen atom or a C1-C 10 The organic group is more preferably a hydrogen atom or a C1-C5 organic group. Here, the organic group is not particularly limited as long as it contains 1 to 20 carbon atoms. Examples include straight chain or branched alkyl, straight chain or branched aryl, -OCOCH3 and -CN. The organic group may contain heteroatoms, such as oxygen atoms. R 6 and R 7 Preferably, methyl, R 8 Preferred is a hydrogen atom.
[0075] The lactone ring unit can be introduced into the methacrylic copolymer by the methods described in JP2000-230016A, JP2001-151814A, JP2002-120326A, JP2002-254544A, JP2005-146084A, etc., for example, by intramolecular cyclization of a structural unit derived from 2-(hydroxyalkyl)acrylate and a structural unit derived from methyl methacrylate.
[0076] In addition to the structural unit (R) and the like, the methacrylic copolymer (A) according to the present invention may further include a glutaric anhydride unit as another vinyl monomer unit. The glutaric anhydride unit is a unit having a 2,6-dioxodihydropyrandiyl structure. Examples of the unit having a 2,6-dioxodihydropyrandiyl structure include the structural unit represented by formula (V).
[0077]
[0078] In formula (V), R 9 Each is independently a hydrogen atom or a C1-C5 alkyl group, preferably a methyl group.
[0079] The unit having a 2,6-dioxodihydropyrandiyl structure can be introduced into the methacrylic copolymer by the methods described in JP2007-197703A, JP2010-96919A, etc., for example, by intramolecular cyclization of two adjacent structural units derived from (meth)acrylic acid, or by intramolecular cyclization of a structural unit derived from (meth)acrylic acid and a structural unit derived from methyl (meth)acrylate.
[0080] The other vinyl monomer units copolymerizable with the methyl methacrylate unit may be used alone or in combination of two or more.
[0081] In the methacrylic copolymer (A) according to the present invention, the ratio of the additional vinyl monomer units copolymerizable with the methyl methacrylate units is preferably 0 to 20% by mass, more preferably 0 to 15% by mass, and further preferably 0 to 10% by mass, based on all structural units. If the ratio of the additional vinyl monomer units copolymerizable with the methyl methacrylate units in the methacrylic copolymer is greater than 20% by mass, heat resistance and rigidity are reduced. The ratio of each monomer unit can be determined by, for example 1 H-NMR, 13 C-NMR or infrared spectroscopy.
[0082] The weight average molecular weight (M w ) is preferably 40,000 to 250,000, more preferably 50,000 to 200,000, and further more preferably 60,000 to 180,000. w When M is 40,000 or more, the resin composition of the present invention has excellent impact resistance. w When it is 250,000 or less, the resin composition of the present invention has enhanced fluidity, resulting in improved molding processability.
[0083] Weight average molecular weight (M w ) is a value calculated by converting a chromatogram measured by gel permeation chromatography into a molecular weight of a corresponding standard polystyrene.
[0084] In the methacrylic copolymer (A) according to the present invention, the lower limit of the glass transition temperature is preferably 130° C., more preferably 135° C., and further preferably 140° C. The upper limit of the glass transition temperature is not particularly limited, but is preferably 170° C.
[0085] In this specification, the glass transition temperature (Tg) is measured in accordance with JIS K 7121. Specifically, a DSC curve is measured under the following conditions: the methacrylic copolymer is first heated to 230° C., then cooled to room temperature, and then heated from room temperature to 230° C. at a heating rate of 10° C. / min. The midpoint determined from the DSC curve measured during the second heating period is obtained as the glass transition temperature (Tg).
[0086] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic copolymer (A) according to the present invention is preferably in the range of 1.0 to 30 g / 10 minutes. The lower limit of MFR is more preferably 1.5 g / 10 minutes or more, and further more preferably 2.0 g / 10 minutes or more. The upper limit of MFR is more preferably 25 g / 10 minutes or less, and further more preferably 20 g / 10 minutes or less. When MFR is in the range of 1.0 to 30 g / 10 minutes, hot melt forming is stably performed in an excellent manner. The MFR used in this specification is a value measured at a temperature of 230°C and under a load of 3.8 kg using a melt indexer in accordance with JIS K 7210.
[0087] The methacrylic copolymer (A) according to the present invention can be obtained by, for example, subjecting a copolymer (which may be referred to as a "precursor polymer" in this specification) of a starting monomer material containing methyl methacrylate (MMA), α-methylstyrene (αMSt) and styrene (St) or maleic anhydride (Mah) to a ring structure-forming reaction.
[0088] Specifically, the manufacturing method includes the following steps: continuously supplying a reactant containing a monomer mixture (containing 51 to 98% by mass of methyl methacrylate, 1 to 48% by mass of α-methylstyrene, and 1 to 48% by mass of styrene or maleic anhydride), a free radical polymerization initiator, and a chain transfer agent as necessary to a tank reactor; bulk polymerization of the monomer mixture is performed in the tank reactor to achieve a polymerization conversion rate of 30 to 60% by mass, thereby obtaining a reaction product; removing the monomer mixture in the reaction product to obtain a precursor polymer; and subjecting the obtained precursor polymer to a ring structure formation reaction. Each step can be performed using known techniques.
[0089] The precursor polymer is a polymer obtained by polymerizing reactants comprising a monomer mixture and an optional free radical polymerization initiator and a chain transfer agent. The monomer mixture contains 51 to 98 mass %, preferably 55 to 95 mass % of methyl methacrylate. The monomer mixture contains 48 to 1 mass %, preferably 40 to 3 mass % of α-methylstyrene. In addition, the monomer mixture contains 48 to 1 mass % of styrene or maleic anhydride.
[0090] The polymerization initiator used is not particularly limited as long as it generates reactive radicals. Examples include peroxide-based initiators such as diisopropylbenzene hydroperoxide and tert-butyl hydroperoxide, and azo-based initiators such as 2,2'-azobis(2-methylpropionitrile).
[0091] The polymerization initiator used preferably has a polymerization temperature of 5.1×10 −5 to 2.4×10 −4The average uncleaved initiator concentration is in the range of (mol / L).
[0092] The amount of the polymerization initiator used is adjusted according to the polymerization temperature, and the polymerization initiator is added to the monomer mixture to achieve the above initiator concentration.
[0093] The chain transfer agent used is preferably a monofunctional alkyl mercaptan, such as n-octyl mercaptan or n-dodecyl mercaptan. These chain transfer agents can be used alone or in combination of two or more. Based on 100 parts by mass of the monomer mixture, the amount of the chain transfer agent is preferably 0 to 1 part by mass, more preferably 0.005 to 0.5 parts by mass, and further preferably 0.01 to 0.3 parts by mass.
[0094] The temperature in the tank reactor, that is, the temperature of the liquid in the reaction tank, is preferably 110 to 145° C., more preferably 120 to 140° C. The temperature of the liquid in the reaction tank is preferably within the above range from the viewpoint of easy production of the α-methylstyrene-containing polymer and heat resistance.
[0095] The bulk polymerization in the tank reactor is performed until a polymerization conversion rate of 30 to 65% by mass, preferably 35 to 60% by mass is achieved.
[0096] The average residence time (θ) of the reactants in the tank reactor is preferably 1.5 to 5 hours, more preferably 2 to 4.5 hours, and further preferably 2.5 to 4 hours. From the viewpoint of reducing the required amount of the polymerization initiator, reducing the amount of the polymerization initiator to more easily control the polymerization reaction and control the molecular weight, and from the viewpoint of shortening the time required for the reaction to reach a steady state to improve productivity, the average residence time (θ) of the reactants in the tank reactor is preferably within the above range. The average residence time can be adjusted according to the capacity of the tank reactor and the amount of the reactants supplied.
[0097] The bulk polymerization is preferably performed in an inert gas atmosphere such as nitrogen.
[0098] The manufacturing method according to the present invention includes a step of removing the monomer mixture in the reaction product. The removal method is not particularly limited, and is preferably a heating devolatilization method. After removing the monomer mixture, in order to facilitate the treatment as a molding material, the methacrylic copolymer composition can be made into particles or the like according to a known method. The content of the monomer mixture in the obtained resin composition is preferably 1% by mass or less, more preferably 0.5% by mass or less.
[0099] The lower limit of the glass transition temperature of the precursor polymer is preferably 110°C, more preferably 115°C, and further preferably 120°C. The upper limit is preferably 150°C. The glass transition temperature can be changed by adjusting, for example, the molecular weight and the amount of α-methylstyrene used for copolymerization. The higher the glass transition temperature of the precursor polymer, the higher the heat resistance. The methacrylic copolymer (A) obtained using a precursor polymer with a high glass transition temperature has high heat resistance even when a small amount of structural units (R) is used, so the fluidity is not easily reduced.
[0100] The precursor polymer is not particularly limited as long as the total content of structural units derived from methyl methacrylate is 50 to 98% by mass, the total content of structural units derived from α-methylstyrene is 48 to 1% by mass, and the total content of structural units derived from styrene or maleic anhydride is 48 to 1% by mass. From the viewpoint of polymerizability, transparency, etc., the total content of structural units derived from methyl methacrylate in the methacrylic copolymer (A) is preferably 50% by mass or more and 98% by mass or less, more preferably 55% by mass or more and 95% by mass or less, and most preferably 60% by mass or more and 90% by mass or less.
[0101] The total content of the structural units derived from α-methylstyrene in the precursor polymer is preferably 1% by mass or more and 48% by mass or less, and more preferably 3% by mass or more and 40% by mass or less from the viewpoints of heat resistance, polymerizability, water absorption, etc. From the viewpoint of obtaining a methacrylic copolymer (A) having sufficient heat resistance and from the viewpoint of polymerizability, the structural units derived from α-methylstyrene are preferably within the above range.
[0102] The total content of the structural units derived from styrene or maleic anhydride in the precursor polymer is preferably 1% by mass or more and 48% by mass or less, more preferably 3% by mass or more and 40% by mass or less from the viewpoints of heat resistance, fluidity, thermal stability, etc. From the viewpoints of improving the polymerization rate, improving the thermal decomposition resistance, and improving the heat resistance of the methacrylic copolymer (A), the structural units derived from styrene or maleic anhydride are preferably within the above range.
[0103] The precursor polymer has a weight average molecular weight M in terms of polystyrene in a chromatogram obtained by gel permeation chromatography. w The weight average molecular weight M is preferably 30,000 or more and 200,000 or less, more preferably 40,000 or more and 180,000 or less, and still more preferably 50,000 or more and 160,000 or less. w It is preferably within the above range. wThe amount of the polymerization initiator and / or the chain transfer agent (optional component) used in the production of the precursor polymer can be controlled by adjusting the type, amount, addition time, etc.
[0104] The ring structure forming reaction can be carried out using, for example, an extruder. The example of the extruder includes a single screw extruder, a twin screw extruder and a multi-screw extruder. From the viewpoint of mixing performance, a twin screw extruder is preferred. The example of the twin screw extruder includes a non-meshing co-rotating extruder, a meshing co-rotating extruder, a non-meshing counter-rotating extruder and a meshing counter-rotating extruder. A meshing co-rotating extruder is preferred because it can rotate at high speed and can effectively promote mixing. These extruders can be used alone or in series.
[0105] In the ring structure forming reaction using an extruder, for example, the precursor polymer as the starting material is fed from the starting material feeding section of the extruder. After the precursor polymer is melted and fills the inside of the barrel, an imidizing agent (optional component) etc. can be injected into the extruder using an addition pump, so that the ring structure forming reaction is carried out in the extruder. When an imidizing agent is used, the structural unit (R) comprises an N-substituted or unsubstituted glutarimide unit, and if necessary, an N-substituted or unsubstituted maleimide unit, a lactone ring unit and / or a glutaric anhydride unit can be included. Based on 100 parts by mass of the methacrylic copolymer, the amount of the imidizing agent is 1.6 to 30 parts by mass, preferably 2.0 to 20 parts by mass. When the amount of the imidizing agent is within the above range, the byproduct of the methacrylamide unit can be suppressed.
[0106] The resin temperature in the reaction zone of the extruder is preferably set in the range of 180 to 300° C., more preferably 200 to 280° C. The resin temperature in the reaction zone is preferably within the above range from the viewpoint of suppressing the decrease in the reaction efficiency of the ring structure forming reaction, suppressing the decrease in the heat resistance of the methacrylic copolymer due to the by-production of the methacrylamide unit, and suppressing the decrease in the mechanical strength of the obtained molded body containing the methacrylic copolymer (A) by suppressing the decomposition of the resin. It should be noted that the reaction zone of the extruder refers to the area from the injection position for injecting the imidizing agent, etc. to the resin discharge port (die head portion) in the barrel of the extruder.
[0107] By increasing the reaction time in the reaction zone of the extruder, the ring structure formation reaction can be further carried out. The reaction time in the reaction zone of the extruder is preferably greater than 10 seconds, more preferably greater than 30 seconds. When the reaction time is less than 10 seconds, the ring structure formation reaction may be difficult to carry out.
[0108] The resin pressure in the extruder is preferably in the range of atmospheric pressure to 50 MPa, more preferably in the range of 1 to 30 MPa. Considering the mechanical pressure resistance limit of a general extruder, the resin pressure in the extruder is preferably in the above range (especially below the upper limit) from the viewpoint of not requiring special equipment and reducing costs.
[0109] It is preferred to use an extruder having a vent capable of reducing pressure to below atmospheric pressure. With such a configuration, unreacted substances, byproducts such as methanol, and / or monomers can be removed, and the breaking strength of a molded body comprising the resin composition of the present invention tends to be improved.
[0110] For the ring structure forming reaction, a high viscosity reactor such as a horizontal twin-screw reactor (eg, Vyborac manufactured by Sumitomo Heavy Industries, Ltd.) or a vertical twin-screw mixing tank (eg, SuperBlend) can be appropriately used instead of the extruder.
[0111] During the ring structure forming reaction, carboxyl groups may be by-produced in the methacrylic copolymer. If necessary, the carboxyl groups may be converted into ester groups by an esterifying agent, a catalyst, etc. This can reduce the foaming of the resin during the optical film manufacturing process. The ester group may vary depending on the esterifying agent and / or catalyst used, and from the viewpoint of reducing the melt viscosity of the resin during melt forming, the reactivity of esterification, and the heat resistance of the resin after esterification, it is preferred to contain methyl methacrylate units, and more preferably to contain both methyl methacrylate units and ethyl methacrylate units.
[0112] From the viewpoints of cost, reactivity, etc., the esterification agent is preferably dimethyl carbonate.
[0113] The amount of the esterifying agent can be set, for example, so that the methacrylic copolymer has a desired acid value.
[0114] In addition to the esterifying agent, a catalyst can also be used together. The type of catalyst is not particularly limited, and examples include amine compounds such as trimethylamine, triethylamine, monomethyldiethylamine, dimethylmonoethylamine, and dimethylbenzylamine. Among them, triethylamine is preferred from the viewpoints of cost, reactivity, etc.
[0115] Styrene resin (B)
[0116] The content of the styrene resin (B) in the resin composition of the present invention is in the range of 51 to 95% by mass, preferably 55 to 90% by mass, and more preferably 60 to 85% by mass. When the content of the styrene resin (B) is 51% by mass or more, the resin composition of the present invention has excellent impact resistance, and when the content of the styrene resin (B) is 95% by mass or less, the resin composition of the present invention has improved heat resistance and surface hardness.
[0117] The styrene resin (B) according to the present invention is selected from the group consisting of ABS (acrylonitrile-butadiene-styrene) resin, AES (acrylonitrile-EPDM-styrene) resin, ASA (acrylate-styrene-acrylonitrile) resin and AS (acrylonitrile-styrene) resin. These resins can be used alone or in combination of two or more.
[0118] ABS resin, AES resin and ASA resin are graft copolymers in which at least styrene monomer and acrylonitrile monomer are graft copolymerized onto a rubber-like polymer. For example, ABS resin is obtained by using a butadiene-based rubber (e.g., polybutadiene or a styrene-butadiene copolymer) as a rubber-like polymer; AES resin is obtained by using an ethylene-based rubber (e.g., an ethylene-α-olefin copolymer) as a rubber-like polymer; and ASA resin is obtained by using an acrylic rubber (e.g., butyl acrylate or ethyl acrylate) as a rubber-like polymer. Two or more of these rubber-like polymers may also be used in the graft copolymerization.
[0119] The glass transition temperature of the rubber copolymer is preferably 0° C. or lower, more preferably -50° C. or lower, and further preferably -70° C. or lower. The glass transition temperature can be measured by DSC.
[0120] The mass average particle size of the rubber copolymer is not particularly limited, preferably 0.1 to 0.35 μm, more preferably 0.12 to 0.33 μm, and further more preferably 0.15 to 0.3 μm. When the mass average particle size is 0.1 μm or more, the impact resistance is further improved. When the mass average particle size is 0.35 μm or less, the design characteristics (such as blackness) are further improved, and the occurrence of white fog is further suppressed. The mass average particle size can be determined by observing the rubber copolymer under a transmission electron microscope.
[0121] The polymer grafted onto the rubber copolymer is not particularly limited. Examples include acrylonitrile-styrene copolymers, acrylonitrile-α-methylstyrene copolymers, acrylonitrile-styrene-butyl acrylate copolymers, acrylonitrile-styrene-methyl methacrylate copolymers, and acrylonitrile-styrene-N-phenylmaleimide copolymers. Among them, acrylonitrile-styrene copolymers, acrylonitrile-styrene-butyl acrylate copolymers, and acrylonitrile-styrene-methyl methacrylate copolymers are preferred.
[0122] The method for producing the graft copolymer such as ABS resin may be a known method. Examples include production methods by emulsion polymerization and / or continuous bulk polymerization. Specific examples include emulsion graft polymerization, in which the copolymer is graft polymerized onto the latex of the rubber component produced by emulsion polymerization.
[0123] The AS resin is a copolymer having a styrene monomer unit and an acrylonitrile monomer unit, and is, for example, a styrene-acrylonitrile copolymer.
[0124] Examples of other copolymerizable monomers that can be used for the AS resin include: (meth)acrylate monomers such as methyl methacrylate; acrylate monomers such as butyl acrylate and ethyl acrylate; (meth)acrylic acid monomers such as methacrylic acid; acrylic acid monomers such as acrylic acid; and N-substituted maleimide monomers such as N-phenylmaleimide.
[0125] The structural units of the AS resin are preferably such that the styrene monomer unit is 60 to 90 mass % and the acrylonitrile monomer unit is 10 to 40 mass %, and more preferably such that the styrene monomer unit is 65 to 80 mass % and the acrylonitrile monomer unit is 20 to 35 mass %. When the structural units are within the above range, the resulting resin composition has a good balance between impact strength and fluidity. The values of the styrene monomer unit and the acrylonitrile monomer unit are determined by 13 C-NMR determination.
[0126] The method for producing the AS resin may be a known method. For example, it may be produced by bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. The operation mode of the reactor may be continuous, batch, or semi-batch.
[0127] The styrene resin (B) according to the present invention is not particularly limited as long as the above range is met. Since the rubber copolymer is included and excellent impact resistance is thus provided, ABS resin, AES resin and ASA resin are preferred. Since less double bond components are included in the rubber copolymer to achieve excellent weather resistance, AES resin and ASA resin are more preferred. Since when a methacrylic copolymer is added, the reduction in the impact resistance of acrylic rubber is suppressed, and the excellent impact resistance of the resin composition of the present invention is obtained, ASA resin is particularly preferred.
[0128] Methacrylic resin (C)
[0129] Based on the methacrylic copolymer (A) and the styrene resin (B), the resin composition of the present invention may further include or not include a methacrylic resin (C). Therefore, in the present invention, the expression "a resin composition comprising 0 to 30 parts by mass of a methacrylic resin (C)" may also include a resin composition that does not include a methacrylic resin (C). The content of the methacrylic resin (C) in the resin composition of the present invention is in the range of 0 to 30% by mass, preferably 3 to 20% by mass, and more preferably 5 to 15% by mass. In this embodiment, the resin composition of the present invention has excellent surface hardness, surface gloss and fluidity by including the methacrylic resin (C).
[0130] In the present invention, the methacrylic resin (C) refers to a methacrylic resin other than the above-mentioned methacrylic copolymer (A). In one embodiment, the proportion of the structural unit derived from methacrylic acid ester in the methacrylic resin (C) according to the present invention is, for example, 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and further preferably 99% by mass or more. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, pentadecyl methacrylate, dodecyl methacrylate; phenyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, 2-ethoxyethyl methacrylate, glycidyl methacrylate, allyl methacrylate; cyclohexyl methacrylate, norbornene methacrylate and isobornyl methacrylate, preferably methyl methacrylate. These methacrylates may be used alone or in combination of two or more. In addition, the methacrylic resin (C) may contain a structural unit derived from a monomer other than methacrylate. Such other monomers are preferably acrylates. The content of the structural unit derived from acrylate in the methacrylic resin (C) is preferably 20% by mass or less, more preferably 10% by mass or less, further more preferably 5% by mass or less, and most preferably 1.0% by mass or less.
[0131] Examples of such acrylic acid esters include methyl acrylate (hereinafter referred to as "MA"), ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, dodecyl acrylate, stearyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, cyclohexyl acrylate, 2-methoxyethyl acrylate, 3-methoxybutyl acrylate, trifluoromethyl acrylate, trifluoroethyl acrylate, pentafluoroethyl acrylate, glycidyl acrylate, allyl acrylate, phenyl acrylate, toluene acrylate, benzyl acrylate, isobornyl acrylate, and 3-dimethylaminoethyl acrylate. From the viewpoint of availability, MA, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, and tert-butyl acrylate are preferred, MA and ethyl acrylate are more preferred, and MA is most preferred. These acrylic acid esters may be used alone or in combination of two or more.
[0132] The methacrylic resin (C) according to the present invention can be obtained by polymerizing the above-mentioned methacrylate with one or more other optional monomers. For polymerization using two or more monomers, a monomer mixture is usually prepared by mixing the two or more monomers, and the monomer mixture is polymerized. The polymerization method is not particularly limited. From the viewpoint of productivity, free radical polymerization is preferably performed according to a method such as bulk polymerization, suspension polymerization, solution polymerization or emulsion polymerization.
[0133] The weight average molecular weight (hereinafter referred to as "M w ”) is preferably 40,000 to 400,000, more preferably 45,000 to 200,000, and further more preferably 50,000 to 150,000. When M w When M is 40,000 or more, the mechanical strength of the resin composition of the present invention becomes excellent. w When it is 400,000 or less, the resin composition of the present invention becomes excellent in fluidity and has enhanced molding processability.
[0134] The glass transition temperature of the methacrylic resin (C) according to the present invention is preferably 100° C. or higher, more preferably 103° C. or higher, and further preferably 105° C. or higher. Since the glass transition temperature is 100° C. or higher, the resin composition of the present invention has excellent heat resistance. The term "glass transition temperature" in this specification refers to a temperature determined by measuring at a heating rate of 10° C. / min using a differential scanning calorimeter and calculating according to a midpoint method.
[0135] The melt flow rate (hereinafter referred to as "MFR") of the methacrylic resin (C) according to the present invention is preferably in the range of 1 to 30 g / 10 minutes. The lower limit of MFR is more preferably 1.2 g / 10 minutes or more, and further more preferably 1.5 g / 10 minutes. The upper limit of MFR is more preferably 25 g / 10 minutes or less, and further more preferably 22 g / 10 minutes or less. When MFR is in the range of 1 to 30 g / 10 minutes, hot melt forming is stabilized. The term "MFR" in this specification refers to a value measured at a temperature of 230°C and under a load of 3.8 kg using a melt indexer in accordance with JIS K7210.
[0136] Resin composition
[0137] From the viewpoints of heat resistance, surface hardness, fluidity and impact resistance, the mass ratio of the methacrylic copolymer (A) / styrene resin (B) of the resin composition of the present invention is 5 / 95 to 49 / 51, preferably 10 / 90 to 45 / 55, more preferably 15 / 85 to 40 / 60, and further preferably 20 / 80 to 30 / 70.
[0138] The resin composition of the present invention may contain a filler as required, as long as the effect of the present invention is not impaired. Examples of fillers include calcium carbonate, talc, carbon black, titanium oxide, silica, clay, barium sulfate and magnesium carbonate. The amount of filler that can be contained in the resin composition of the present invention is preferably 3% by mass or less, more preferably 1.5% by mass or less.
[0139] The resin composition of the present invention may contain other polymers as long as the effects of the present invention are not impaired. Examples of other polymers include polyolefin resins (e.g., polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene); vinyl ionomers; styrene resins other than those listed as the styrene resin (B) (e.g., polystyrene, styrene-maleic anhydride copolymer, high-impact polystyrene, MBS resin, and SAS resin); methyl methacrylate-styrene copolymers; polyester resins (e.g., polyethylene terephthalate and polybutylene terephthalate); polyamides (e.g., nylon 6, nylon 66, and polyamide elastomers); ); polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyacetal, polyvinylidene fluoride, polyurethane, phenoxy resin, modified polyphenylene ether, polyphenylene sulfide, polysiloxane modified resin; silicone rubber; acrylic multilayer copolymer elastomer; acrylic thermoplastic elastomer (e.g., diblock copolymer and triblock copolymer of methyl methacrylate polymer block-n-butyl acrylate polymer block); styrene thermoplastic elastomer (e.g., SEPS, SEBS and SIS); and olefin rubber (e.g., IR, EPR and EPDM). The amount of such other polymers that can be included in the methacrylic resin composition of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and most preferably 0% by mass.
[0140] The resin composition of the present invention may contain additives such as antioxidants, thermal degradation inhibitors, ultraviolet absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, pigments, light diffusers, organic dyes, matting agents and fluorescent agents as long as the effects of the present invention are not impaired.
[0141] The antioxidant alone has the effect of preventing the resin from oxidative degradation in the presence of oxygen. Examples include phosphorus antioxidants, hindered phenol antioxidants and thioether antioxidants. These antioxidants can be used alone or in combination of two or more. Among them, from the viewpoint of preventing the effect of optical property degradation due to coloring, phosphorus antioxidants, hindered phenol antioxidants, etc. are preferred, and a combination of phosphorus antioxidants and hindered phenol antioxidants is more preferred. The ratio of the phosphorus antioxidant to the hindered phenol antioxidant used in combination is preferably, but not limited to, in the range of 1 / 5 to 2 / 1, and more preferably in the range of 1 / 2 to 1 / 1, in terms of the mass ratio of phosphorus antioxidant / hindered phenol antioxidant.
[0142] Examples of the phosphorus antioxidant include 2,2′-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite (trade name: ADK STAB HP-10, manufactured by Adeka Corporation), tris(2,4-di-tert-butylphenyl) phosphite (trade name: Irgafos 168, manufactured by Ciba Specialty Chemicals), and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (trade name: ADK STAB PEP-36, manufactured by Adeka Corporation).
[0143] Examples of hindered phenol antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (trade name: Irganox 1010, manufactured by Ciba Specialty Chemicals) and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (trade name: Irganox 1076, manufactured by Ciba Specialty Chemicals).
[0144] The thermal degradation inhibitor is a compound that can prevent thermal degradation of the resin by capturing polymer radicals generated when exposed to a high heat environment in a substantially oxygen-free state. Examples of the thermal degradation inhibitor include: 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-hydroxybenzyl)-4-methylphenyl acrylate (trade name: Sumilizer GM, manufactured by Sumitomo Chemical Co., Ltd.), 2,4-di-tert-amyl-6-(3',5'-di-tert-amyl-2'-hydroxy-α-methylbenzyl)phenyl acrylate (trade name: Sumilizer GS, manufactured by Sumitomo Chemical Co., Ltd.), 4-tert-butyl-2-(5-tert-butyl-2-oxo-3H-benzofuran-3-yl)phenyl-3,5-di-tert-butyl-4-hydroxybenzoate (trade name: Revonox 501, manufactured by Qiti Technology Co., Ltd.), 5,7-di-tert-butyl-3-(3,4-dimethylphenyl)-3H-benzofuran-2-one and 5,7-di-tert-butyl-3-(3,4-dipropylphenyl)-3H-benzofuran-2-one (trade name: HP-136, manufactured by BASF).
[0145] The ultraviolet absorber is a compound that has the ability to absorb ultraviolet rays. The ultraviolet absorber is a compound that is considered to have the function of mainly converting light energy into heat energy.
[0146] Examples of ultraviolet absorbers include benzophenones, benzotriazoles, triazines, benzoates, salicylates, cyanoacrylates, oxalylanilides, malonates, and formamidines. They can be used alone or in combination of two or more. Among them, benzotriazoles, triazines, or the maximum value of the molar absorptivity coefficient ε at a wavelength of 380 to 450 nm are preferred. max 1200 dm 3 ∙mol -1 cm -1 The following ultraviolet absorbers.
[0147] The light stabilizer is a compound that is considered to mainly have a function of capturing free radicals formed by photooxidation, and examples include hindered amines such as compounds having a 2,2,6,6-tetraalkylpiperidine skeleton.
[0148] Examples of the lubricant include stearic acid, behenic acid, stearic acid amide, methylene bisstearamide, hydroxystearic acid triglyceride, paraffin, ketone wax, caprylic alcohol and hydrogenated oil.
[0149] The release agent is a compound having the function of making the molded body easy to demold from the mold. Examples include higher alcohols (such as hexadecanol and stearyl alcohol); and higher fatty acid glycerides (such as stearic acid monoglyceride and stearic acid diglyceride). Since higher fatty acid glycerides may cause the formation of gel-like foreign matter, it is preferred to use higher alcohols as release agents.
[0150] The polymer processing aid is a compound effective in achieving thickness accuracy and thinning of the obtained film when the acrylic resin composition is formed. The polymer processing aid can generally be produced by emulsion polymerization. The polymer processing aid is preferably a polymer particle having a particle size of 0.05 to 0.5 μm.
[0151] The polymer particles may be single-layer particles containing a polymer having a single composition ratio and a single intrinsic viscosity, or may be multi-layer particles containing two or more polymers having different composition ratios or intrinsic viscosities. Among them, particles having a double-layer structure consisting of a polymer layer having a low intrinsic viscosity as an inner layer and a polymer layer having a high intrinsic viscosity of 5 dl / g or more as an outer layer are preferred. The polymer processing aid preferably has an intrinsic viscosity of 3 to 6 dl / g. From the viewpoint of obtaining a high moldability improvement effect and avoiding a decrease in the melt fluidity of the resin composition, the intrinsic viscosity is preferably within the above range.
[0152] Examples of the antistatic agent include alkyl sulfonates such as sodium heptyl sulfonate, sodium octyl sulfonate, sodium nonyl sulfonate, sodium decyl sulfonate, sodium dodecyl sulfonate, sodium hexadecyl sulfonate, sodium octadecyl sulfonate, sodium diheptyl sulfonate, potassium heptyl sulfonate, potassium octyl sulfonate, potassium nonyl sulfonate, potassium decyl sulfonate, potassium dodecyl sulfonate, potassium hexadecyl sulfonate, potassium octadecyl sulfonate, potassium diheptyl sulfonate, lithium heptyl sulfonate, lithium octyl sulfonate, lithium nonyl sulfonate, lithium decyl sulfonate, lithium dodecyl sulfonate, lithium hexadecyl sulfonate, lithium octadecyl sulfonate and lithium diheptyl sulfonate.
[0153] Examples of flame retardants include magnesium hydroxide, aluminum hydroxide, hydrated aluminum silicate, hydrated magnesium silicate, metal hydrates having a hydroxyl group or water of crystallization (e.g., hydrotalcite), phosphoric acid compounds (e.g., polyphosphoric acid amine and phosphoric acid esters), and silicon compounds. Preferred are phosphoric acid ester flame retardants such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, tri(xylene) phosphate, dimethyl ethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate.
[0154] Examples of dyes or pigments include organic red pigments (e.g., para red, fire red, pyrazolone red, thioindigo red, and perylene red); organic blue pigments (e.g., cyanine blue, indanthrene blue); organic green pigments (e.g., cyanine green, naphthol green) and black pigments (e.g., carbon black). Black pigments (e.g., carbon black) are preferred. More than one of these can be used.
[0155] The organic dye that can be preferably used is a compound having a function of converting ultraviolet light into visible light.
[0156] Examples of the light diffusing agent and the matting agent include glass particles, polysiloxane cross-linked particles, cross-linked polymer particles, talc, calcium carbonate, and barium sulfate.
[0157] Examples of the fluorescent agent include fluorescent pigments, fluorescent dyes, fluorescent whitening dyes, fluorescent whitening agents, and fluorescent bleaching agents.
[0158] These additives can be used alone or in combination of two or more. These additives can be added to the polymerization reaction solution during the manufacture of methacrylic copolymer (A) or styrene resin (B), can be added to the manufactured methacrylic copolymer (A) and / or styrene resin (B), or can be added during the preparation of the resin composition of the present invention. From the viewpoint of preventing the appearance of the molded body from being bad, the total amount of the additives contained in the resin composition of the present invention is preferably less than 7% by mass of the resin composition, more preferably less than 5% by mass, and further preferably less than 4% by mass.
[0159] The resin composition of the present invention has a Vicat softening temperature measured by the method described in JIS K 7206 B50 method, preferably 105 to 140°C, more preferably 108 to 135°C, and further preferably 110 to 130°C.
[0160] The method for preparing the resin composition of the present invention is not particularly limited. For example, a method for melt mixing the methacrylic copolymer (A) and the styrenic resin (B) can be used. During melt mixing, other polymers, additives, etc. can be mixed as required. The methacrylic copolymer (A) can be mixed with other polymers and additives first, and then mixed with the styrenic resin (B). The styrenic resin (B) can also be mixed with other polymers and additives first, and then mixed with the methacrylic copolymer (A), or other methods can be used. Mixing can be carried out using a known mixing device or mixing device, such as a kneader-ruder, an extruder, a mixing roller or a Banbury mixer. Wherein, a twin-screw extruder is preferred.
[0161] The resin composition of the present invention can be prepared into the form of particles, etc., to increase the convenience during storage, transportation or molding.
[0162] Formed body
[0163] The molded body of the present invention comprises the resin composition of the present invention. The method for manufacturing the molded body of the present invention is not particularly limited. Examples include melt molding methods, such as T-die method (lamination method, coextrusion method, etc.), inflation method (coextrusion method, etc.), compression molding method, blow molding method, calendering method, vacuum molding method, injection molding method (insert method, two-color molding method, pressing method, core-back method, sandwich method, etc.), solution casting method, etc. In melt molding, the resin composition is usually heated to 200 to 280°C and then processed. The heating temperature is preferably 210 to 270°C. Heating is preferably performed to a temperature above the above lower limit to fully devolatilize in a relatively short time. By fully devolatilizing, appearance defects such as silver marks can be prevented from forming on the molded body. In order to avoid appearance defects such as scorching and silver marks caused by thermal decomposition, heating is preferably performed to a temperature below the above upper limit. The resin composition of the present invention has high heat resistance and excellent fluidity; therefore, shear heating during molding is suppressed, and the occurrence of appearance defects of the molded body is suppressed.
[0164] The resin combination of the present invention and the formed body comprising the resin combination can be used for parts of various applications. The specific examples of application include furniture, household goods, storage and emergency supplies, building materials (such as walls and roofs), toys and playground equipment, game applications (such as the panel of a marble game), medical and welfare supplies, office automation equipment, audio-visual equipment, batteries and electrical equipment, lighting equipment, structural parts of ships and aircraft, and automotive interior and exterior parts. In particular, the resin combination of the present invention and the formed body can be suitable for, for example, automotive applications (such as body parts and interior and exterior parts); optical applications; and electrical and electronic applications. The example of the optical application includes various lenses and touch panels and transparent substrates for solar cells, etc.
[0165] Furthermore, the resin composition and molded article of the present invention can also be used in the fields of optical communication systems, optical switching systems, and optical measurement systems, for example, in waveguides, optical fibers, covering materials for optical fibers, LED lenses, and lens covers for EL lighting.
[0166] Examples of electrical and electronic applications include display devices (e.g., personal computers, game consoles, televisions, car navigation systems, electronic paper, mobile phones, and tablet devices), printers, copiers, scanners, dryer vents, electric kettle parts, fax machines, electronic notepads, electronic desktop calculators, electronic dictionaries, cameras, video cameras, battery packs, recording medium drive devices, recording medium reading devices, mice, numeric keypads, CD players, MD players, and portable radios and audio players. In particular, the resin composition and molded article of the present invention can be applied to the design parts of the housings of televisions, personal computers, car navigation systems, electronic paper, mobile phones, tablet devices, etc.
[0167] For vehicle applications, the resin composition and molded body of the present invention can be suitable for automotive interior parts (such as automotive side visors, rear visors, head wings, headlight covers, instrument panel peripheral parts, air conditioning vents, instrument panels and console boxes) and automotive exterior parts (such as rearview mirror housings, spoilers, pillar trims, wheel covers, rear light covers, bumpers, front grilles, rear grilles and license plate trims).
[0168] Example
[0169] The present invention will be described in more detail with reference to Examples. However, the present invention is not limited to the Examples.
[0170] Physical properties and the like were measured by the following methods.
[0171] Polymerization conversion rate
[0172] A chromatography column InertCap 1 (df=0.4 μm, 0.25 mm ID×60 m; manufactured by GL Sciences) was connected to a GC-14A gas chromatograph (manufactured by Shimadzu Corporation) to perform analysis under the following conditions, and calculation was performed based on the analysis.
[0173] Injection temperature = 250℃
[0174] Detector temperature = 250°C
[0175] Temperature conditions: maintain the temperature at 60°C for 5 minutes, increase the temperature to 250°C at 10°C / min, and then maintain at 250°C for 10 minutes
[0176] Unit composition of precursor polymer
[0177] pass 13 C NMR determines the carbon ratios of the phenyl group in the α-methylstyrene unit, the carbonyl group in the methyl methacrylate unit, the phenyl group in the styrene unit, and the carbonyl group in the maleic anhydride unit, and the unit composition is calculated based on the carbon ratios.
[0178] Weight average molecular weight
[0179] 4 mg of the resin to be tested was dissolved in 5 ml of tetrahydrofuran to prepare a sample solution. The column oven temperature was set to 40°C, 20 μl of the sample solution was injected into the instrument at an eluent flow rate of 0.35 ml / min, and a chromatogram was obtained by GPC (gel permeation chromatography). Ten different polystyrene standards with molecular weights ranging from 400 to 5,000,000 were measured by GPC, and a calibration curve showing the relationship between retention time and molecular weight was prepared. The M of the resin to be tested was determined based on the calibration curve. w .
[0180] Instrument: HLC-8320 GPC instrument, manufactured by Tosoh Corporation
[0181] Separation column: TSK guard column Super HZ-H, TSKgel HZM-M and TSKgel Super HZ4000 (manufactured by Tosoh Corporation) connected in series
[0182] Eluent: Tetrahydrofuran
[0183] Eluent flow rate: 0.35 mL / min
[0184] Column temperature: 40°C
[0185] Detection method: Differential refractive index (RI)
[0186] Unit composition of methacrylic acid copolymer
[0187] The α-methylstyrene unit and the styrene unit have the same composition as the respective unit compositions of the precursor polymer.
[0188] use 1 The methacrylic acid copolymers were analyzed by H-NMR (trade name: UltraShield 400 Plus, manufactured by Bruker Corporation). 1 H-NMR measurement is used to determine the content (mol%) of each monomer unit in the methacrylic copolymer, such as imide (glutarimide and maleimide) unit, methyl methacrylate unit and aromatic vinyl (α-methylstyrene and styrene) unit, and the mol% content is converted into weight% content based on the molecular weight of each monomer unit. In addition, an infrared spectrophotometer is used to measure the content of each monomer unit by infrared spectroscopy at about 1700 cm -1 The absorption intensity of the peak derived from the carbonyl unit of maleimide at about 1780 cm -1 The imidization rate (R m ). Use by 13 The maleic anhydride content (m) and imidization rate (R) of the precursor polymer determined by C-NMR m ), and the amount of maleic anhydride (M) in the methacrylic acid copolymer was calculated according to the following formula.
[0189] Maleic anhydride amount (M) = m×(100−R m ) / 100
[0190] Furthermore, using an infrared spectrophotometer, the -1 The absorption intensity of the peak derived from the carbonyl group of glutarimide at about 1700 cm -1 The ratio of glutarimide units to maleimide units in the methacrylic copolymer was determined by measuring the absorption intensity of the peak derived from the carbonyl unit of maleimide at 40°C. 1 The content of the imide unit and the content of the maleimide unit in the methacrylic copolymer are determined by H-NMR.
[0191] Glass transition temperature; Tg
[0192] The resin obtained in the manufacturing example was dissolved in chloroform, reprecipitated with methanol, and then the precipitated resin was vacuum dried at 100°C for more than 12 hours. According to JIS K 7121, a differential scanning calorimeter (model: DSC-50, manufactured by Shimadzu Corporation) was used to measure the DSC curve under the following conditions: the vacuum-dried resin was first heated to 250°C, then cooled to room temperature, and then heated from room temperature to 200°C at 10°C / min. The glass transition temperature at the midpoint determined by the DSC curve measured during the second temperature increase is defined as the glass transition temperature of the present invention.
[0193] Melt flow rate; MFR
[0194] The resin obtained in the production example was dissolved in chloroform and reprecipitated with methanol, and then the precipitated resin was vacuum dried at 100° C. for 12 hours or more. The vacuum dried resin was measured at 230° C. and under a load of 3.8 kg in accordance with JIS K 7210.
[0195] Flexural modulus
[0196] The resins obtained in the manufacturing examples, embodiments and comparative examples were press-formed and then cut to obtain test pieces having a thickness of 4 mm, a length of 80 mm and a width of 10 mm. The flexural modulus (MPa) was measured by three-point bending of each test piece at 23° C. using an autograph (manufactured by Shimadzu Corporation) according to the method described in JIS K 7171.
[0197] Charpy impact strength
[0198] The resins obtained in the manufacturing examples, embodiments and comparative examples were press-formed and then cut to obtain test pieces with a thickness of 4 mm, a length of 80 mm and a width of 10 mm. Each test piece was measured at 23°C and a relative humidity of 50% according to the method described in JIS K 7111. The measurement under the test condition with a notch was carried out in accordance with JIS K 7111-1 / 1eA. The measurement under the test condition without a notch was carried out in accordance with JIS K 7111-1 / 1eU. "NB" means not brake. The measurement was carried out 10 times and the average value was taken as the Charpy impact value.
[0199] Surface hardness
[0200] The resins obtained in Examples and Comparative Examples were press-molded to obtain test pieces having a thickness of 3 mm, a length of 200 mm, and a width of 100 mm. The pencil hardness of each test piece was measured under a load of 0.75 kg in accordance with JIS K 5600-5-4.
[0201] Vicat softening temperature
[0202] The resins obtained in the examples and comparative examples were press-formed and then cut to obtain test pieces having a thickness of 4 mm, a length of 80 mm, and a width of 10 mm. The Vicat softening temperature of each test piece was measured using a 3M-2 HDT tester manufactured by Toyo Seiki Seisaku-sho Co., Ltd. in accordance with the method described in JISK 7206 B50 method.
[0203] Injection moldability
[0204] The resins obtained in the examples and comparative examples were injection molded 200 times using an injection molding machine (M-100C, manufactured by Meiki Co., Ltd.) in a flat mold (steel material: NAK80, molded body size: 40 mm × 200 mm × 2 mm) at a barrel temperature of 250°C and a mold temperature of 50°C, without holding pressure (underfilling). After molding, the degree of contamination on the mold surface was visually observed and evaluated according to the following indicators.
[0205] Evaluation indicators of mold contamination
[0206] A: No mold contamination was observed or slight mold contamination was observed.
[0207] B: Obvious mold contamination was observed.
[0208] The resins obtained in the examples and comparative examples were injection molded using an injection molding machine (M-100C, manufactured by Meiki Co., Ltd.) at a barrel temperature of 270° C., a mold temperature of 55° C., and a molding cycle of 1 minute to produce a flat plate having a length of 205 mm, a width of 160 mm, and a thickness of 0.5 mm. The ratio of the resin flow length (190 mm) to the thickness was 380.
[0209] The appearance of the flat plate was visually observed. The formability was evaluated based on whether the flat plate had forming defects such as sink marks due to insufficient fluidity and silver streaks due to insufficient thermal decomposition resistance.
[0210] Evaluation index of formability
[0211] A: No sink marks or silver streaks were observed.
[0212] B: Sink marks or silver streaks were observed.
[0213] Injection moldability was evaluated based on the evaluation results of mold contamination and moldability.
[0214] Evaluation index of injection moldability
[0215] A: The evaluation indexes of mold contamination and formability are both A.
[0216] B: Either one of the evaluation indicators of mold contamination or formability is A.
[0217] C: The evaluation indexes of mold contamination and formability are both B.
[0218] Glossiness
[0219] The resins obtained in the examples and comparative examples were injection molded using an injection molding machine (M-100C, manufactured by Meiki Co., Ltd.) at a barrel temperature of 240 to 260° C. and a mold temperature of 80° C. to obtain test pieces. The appearance of the test pieces was visually evaluated, and the glossiness of the surface of the test pieces was measured. Then, the evaluation was performed according to the following indices.
[0220] A: Glossiness was observed (visually evaluated as glossy, or the glossiness value was 70 or more).
[0221] B: No gloss was observed (visually evaluated as no gloss, or the gloss value was less than 70).
[0222] Glossiness measurement: Glossiness was measured at a measurement angle of 60° using an appearance analyzer (Rhopoint IQ-S, manufactured by Konica Minolta Inc.) in accordance with JIS Z 8741.
[0223] Materials List
[0224] The following materials are used for the methacrylic copolymer (A), the maleimide-based heat-resistant agent, the styrene resin (B) and the methacrylic resin (C) according to the present invention.
[0225] - Methacrylic acid copolymer (A-7): Delpet PM120N, manufactured by Asahi Kasei Corporation
[0226] (MMA copolymerization ratio = 86%, styrene copolymerization ratio = 7%, N-phenylmaleimide copolymerization ratio = 7%, Tg = 132°C, MFR = 1.2g / 10min, flexural modulus = 3500MPa, notched Charpy impact strength = 1.2kJ / m 2 , notched Charpy impact strength = 16kJ / m 2 )
[0227] - Methacrylic acid copolymer (A-8): Pleximid TT50, manufactured by Polyplastics-Evonik
[0228] (MMA copolymerization ratio = 30%, N-methylglutarimide copolymerization ratio = 70%, Tg = 151°C, MFR = 0.6g / 10min, flexural modulus = 4000MPa, notched Charpy impact strength = 1.3kJ / m 2 , notched Charpy impact strength = 20kJ / m2 )
[0229] - Maleimide heat stabilizer: Polyimilex PSX0371, manufactured by Nippon Shokubai Co., Ltd.
[0230] (N-phenylmaleimide copolymerization ratio = 49%, styrene copolymerization ratio = 50%, maleic anhydride copolymerization ratio = 1%, Tg = 202°C, MFR = 0.1 g / 10 min (2.6 g / 10 min at 265°C))
[0231] - Styrene resin (B-1) (ABS): UMG ABS EX18A, manufactured by DAKENEN U-Ryoto Co., Ltd.
[0232] - Styrene resin (B-2) (AES): Dialac SK30, manufactured by DAKENEN YURITO CO., LTD.
[0233] - Styrene resin (B-3) (ASA): Dialac S310, manufactured by DAKONENG YULINGTU CO., LTD.
[0234] - Styrene resin (B-4) (AS): Denka AS AS-C-800, manufactured by Denka Co., Ltd.
[0235] - Methacrylic resin (C): Parapet, manufactured by Kuraray Co., Ltd.
[0236] (M w =89,000, MMA copolymerization ratio = 99.3%, MA copolymerization ratio = 0.7%, Tg = 118°C, MFR = 2.3g / 10min, flexural modulus = 3300MPa, notched Charpy impact strength = 1.3kJ / m 2 , notched Charpy impact strength = 22kJ / m 2 )
[0237] Production Example: Precursor polymer
[0238] Precursor polymers a-1 to a-5 of Production Examples were produced by the following method.
[0239] Precursor polymer a-1
[0240] 77.5 parts by mass of purified methyl methacrylate (MMA), 17.5 parts by mass of α-methylstyrene (αMSt), 5.0 parts by mass of styrene (St), 0.04 parts by mass of 2,2′-azobis(2-methylpropionitrile) (AIBN), and 0.053 parts by mass of n-octyl mercaptan (n-OM) were placed in an autoclave equipped with a stirrer and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reactants to remove dissolved oxygen to 3ppm. Subsequently, a continuous flow tank reactor equipped with a brine cooling condenser was purged with nitrogen. The polymerization raw material was continuously supplied to the tank reactor at a constant flow rate so that the average residence time was 2.5 hours, thereby performing bulk polymerization at a polymerization temperature of 140°C, and continuously discharging a liquid containing a precursor polymer from the tank reactor. The pressure in the tank reactor was controlled by a pressure regulating valve connected to the brine cooling condenser. The polymerization conversion results are shown in Table 1. Subsequently, the liquid discharged from the reactor was heated to 210° C. and supplied to a twin-screw extruder controlled at 230° C. In the twin-screw extruder, volatile components mainly composed of unreacted monomers were separated and removed, and the precursor polymer was extruded into strands. The strands were cut with a pelletizer to obtain a precursor polymer a-1. The weight average molecular weight M of the obtained precursor polymer a-1 was measured. w . Table 1 shows the results. In addition, a precursor polymer a-2 was obtained in the same manner as the method for producing the precursor polymer a-1, except that 68.0 parts by mass of purified methyl methacrylate (MMA), 28.0 parts by mass of α-methylstyrene (αMSt), 7.0 parts by mass of styrene (St), 0.05 parts by mass of 2,2′-azobis(2-methylpropionitrile) (AIBN) and 0.01 parts by mass of n-octyl mercaptan (n-OM) were used. In addition, a precursor polymer a-3 was obtained in the same manner as the method for producing the precursor polymer a-1, except that 73.0 parts by mass of purified methyl methacrylate (MMA), 13.0 parts by mass of α-methylstyrene (αMSt), 14.0 parts by mass of styrene (St), 0.03 parts by mass of 2,2′-azobis(2-methylpropionitrile) (AIBN) and 0.12 parts by mass of n-octyl mercaptan (n-OM) were used. Polymerization conversion rate and weight average molecular weight M of precursor polymers a-2 and a-3 w Also shown in Table 1.
[0241] Precursor polymer a-4
[0242] 60.0 parts by mass of purified methyl methacrylate (MMA), 25.0 parts by mass of α-methylstyrene (αMSt), 15.0 parts by mass of maleic anhydride (Mah), 0.005 parts by mass of 2,2′-azobis(2-methylpropionitrile) (AIBN) and 0.02 parts by mass of n-octyl mercaptan (n-OM) were placed in an autoclave equipped with a stirrer and uniformly dissolved to obtain a polymerization raw material. Nitrogen was blown into the reactants to remove dissolved oxygen to 3ppm. Subsequently, a continuous flow tank reactor equipped with a brine cooling condenser was purged with nitrogen. The polymerization raw material was continuously supplied to the tank reactor at a constant flow rate so that the average residence time was 2 hours, thereby performing bulk polymerization at a polymerization temperature of 130°C, and continuously discharging a liquid containing a precursor polymer from the tank reactor. The pressure in the tank reactor was controlled by a pressure regulating valve connected to the brine cooling condenser. The polymerization conversion results are shown in Table 1. Subsequently, the liquid discharged from the reactor was heated to 230° C. and supplied to a twin-screw extruder controlled at 240° C. In the twin-screw extruder, volatile components mainly composed of unreacted monomers were separated and removed, and the precursor polymer was extruded into strands. The strands were cut with a pelletizer to obtain a precursor polymer. The weight average molecular weight M of the obtained precursor polymer was measured. w Table 1 shows the results.
[0243] Precursor polymer a-5
[0244] According to the method for producing copolymer (A) described in the examples of JP2003-231785A, polymerization of MS resin (copolymer of methyl methacrylate (MMA) and styrene (St)) was performed. The mass ratio of MMA to St placed in the autoclave was changed to obtain precursor polymer a-5. Table 1 shows the results.
[0245] Production Example 1
[0246] The precursor polymer (a-1) is fed into the conveying unit of a twin-screw extruder (trade name: TEX30α-77AW-3V, manufactured by Nippon Steel Works) equipped with a conveying unit, a melt-mixing unit, a volatilization unit and a discharge unit and set to a screw speed of 150 rpm and a temperature of 230°C to 250°C at a rate of 15 kg / hour. In the melt-mixing unit provided with a mixing device, the amount of monomethylamine is adjusted to give the content of the structural unit derived from glutarimide shown in Table 1, and the monomethylamine is injected into the additive feed port of the twin-screw extruder to react the precursor polymer (a-1) with the monomethylamine. The melt-mixing unit is mainly composed of a mixing disk, and sealing elements are attached to both ends. In the volatilization unit, by-products and excess monomethylamine are volatilized from the molten resin that has passed through the melt-mixing unit and discharged through multiple exhaust ports.
[0247] The molten resin extruded in the form of strands from a die head provided at the end of a discharge unit of a twin-screw extruder was cooled in a water tank and then cut with a granulator to obtain a granular methacrylic copolymer (A-1). In the methacrylic copolymer (A-1), the content of the structural unit derived from glutarimide was 21% by weight. Table 1 shows the composition and physical properties of the methacrylic copolymer (A-1).
[0248] Production Example 2
[0249] A methacrylic acid copolymer (A-2) was obtained in the same manner as in Example 1, except that the precursor polymer (a-2) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 50% by weight. Table 1 shows the composition and physical properties of the methacrylic acid copolymer (A-2).
[0250] Production Example 3
[0251] A methacrylic acid copolymer (A-3) was obtained in the same manner as in Example 1, except that the precursor polymer (a-2) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 70 wt %. Table 1 shows the composition and physical properties of the methacrylic acid copolymer (A-3).
[0252] Production Example 4
[0253] A methacrylic acid copolymer (A-4) was obtained in the same manner as in Example 1, except that the precursor polymer (a-3) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 36 wt %. Table 1 shows the composition and physical properties of the methacrylic acid copolymer (A-4).
[0254] Production Example 5
[0255] A methacrylic copolymer (A-5) was obtained in the same manner as in Example 1, except that the precursor polymer (a-4) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 15 wt % and the content of the structural unit derived from maleimide was 15 wt %. Table 1 shows the composition and physical properties of the methacrylic copolymer (A-5).
[0256] Production Example 6
[0257] A methacrylic acid copolymer (A-6) was obtained in the same manner as in Example 1, except that the precursor polymer (a-5) was used and the amount of monomethylamine added was changed so that the content of the structural unit derived from glutarimide was 42 wt %. Table 1 shows the composition and physical properties of the methacrylic acid copolymer (A-6).
[0258]
[0259] Examples 1 to 6
[0260] Methacrylic acid copolymers (A-1) to (A-5), styrene resin (B-1) and methacrylic acid resin (C) were mixed according to the formulation shown in Table 2, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and a shaft diameter of 62.5 mm to obtain resin compositions (1) to (6). Table 2 shows the composition and physical properties of the resin composition and the evaluation results of the molded product.
[0261] Comparative Examples 1 to 5
[0262] Methacrylic acid copolymers (A-6) to (A-8), styrene resin (B-1) and maleimide heat-resistant agent were mixed according to the formulation shown in Table 2, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and an axis diameter of 62.5 mm to obtain resin compositions (7) to (11). Table 2 shows the composition and physical properties of the resin compositions and the evaluation results of the molded bodies.
[0263]
[0264] Examples 7 to 12
[0265] Methacrylic copolymers (A-1) to (A-5), styrene resin (B-2) and methacrylic resin (C) were mixed according to the formulation shown in Table 3, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and a shaft diameter of 62.5 mm to obtain resin compositions (12) to (17). Table 3 shows the composition and physical properties of the resin compositions and the evaluation results of the molded products.
[0266] Comparative Examples 6 to 10
[0267] Methacrylic acid copolymers (A-6) to (A-8), styrene resin (B-1) and maleimide heat-resistant agent were mixed according to the formulation shown in Table 3, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and an axis diameter of 62.5 mm to obtain resin compositions (18) to (22). Table 3 shows the composition and physical properties of the resin composition and the evaluation results of the molded body.
[0268]
[0269] Examples 13 to 18
[0270] Methacrylic copolymers (A-1) to (A-5), styrene resin (B-2) and methacrylic resin (C) were mixed according to the formulation shown in Table 4, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and a shaft diameter of 62.5 mm to obtain resin compositions (23) to (28). Table 4 shows the composition and physical properties of the resin compositions and the evaluation results of the molded products.
[0271] Comparative Examples 11 to 15
[0272] Methacrylic acid copolymers (A-6) to (A-8), styrene resin (B-1) and maleimide heat-resistant agent were mixed according to the formulation shown in Table 4, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and an axis diameter of 62.5 mm to obtain resin compositions (29) to (33). Table 4 shows the composition and physical properties of the resin compositions and the evaluation results of the molded bodies.
[0273]
[0274] Examples 19 to 24
[0275] Methacrylic copolymers (A-1) to (A-5), styrene resin (B-2) and methacrylic resin (C) were mixed according to the formulation shown in Table 5, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and a shaft diameter of 62.5 mm to obtain resin compositions (34) to (39). Table 5 shows the composition and physical properties of the resin compositions and the evaluation results of the molded products.
[0276] Comparative Examples 16 to 20
[0277] Methacrylic acid copolymers (A-6) to (A-8), styrene resin (B-1) and maleimide heat-resistant agent were mixed according to the formulation shown in Table 5, and the mixture was melt-kneaded and extruded at 230° C. using a twin-screw extruder with an L / D ratio of 32.5 and a shaft diameter of 62.5 mm to obtain resin compositions (40) to (44). Table 5 shows the composition and physical properties of the resin compositions and the evaluation results of the molded bodies.
[0278]
[0279] The methacrylic copolymers (A-1) to (A-5) obtained in Manufacturing Examples 1 to 5 have high heat resistance, rigidity and fluidity. Since a ring structure is formed by an imide cyclization reaction in the extrusion reaction, these methacrylic copolymers do not contain volatile components derived from cyclic monomers. These methacrylic copolymers also have excellent compatibility with styrene resins (B-1) to (B-4). The resin composition obtained in the embodiment comprises a methacrylic copolymer and a styrene resin having such excellent properties, and therefore has excellent heat resistance, surface hardness, injection moldability and glossiness. In addition, the impact resistance of the styrene resin is not significantly impaired. For these reasons, the resin composition is suitable for use as an extruded sheet, an injection molding material and other automotive interior and exterior parts. In contrast, the methacrylic copolymer (A-6) obtained in Manufacturing Example 6 does not contain an αMSt component, and therefore has low heat resistance and poor compatibility with styrene resins (B-1) to (B-4). The resin compositions of Comparative Examples 1, 6, 11 and 16 contain methacrylic copolymer (A-6), which has low impact resistance and poor gloss. Methacrylic copolymer (A-7) has low heat resistance. Methacrylic copolymer (A-7) does not contain αMSt component, so it has poor compatibility with styrene resins (B-1) to (B-4). In addition, since the cyclic monomer is copolymerized, the methacrylic copolymer (A-7) contains a large amount of volatile components. The resin compositions of Comparative Examples 2, 7, 12 and 17 containing methacrylic copolymer (A-7) have low impact resistance and produce a large amount of gas during molding, resulting in mold contamination. The gloss of these resin compositions is also poor. Methacrylic copolymer (A-8) has low fluidity. Methacrylic copolymer (A-8) does not contain αMSt component, so it has poor compatibility with styrene resins (B-1) to (B-4). The resin compositions of Comparative Examples 3, 8, 13 and 18 containing methacrylic copolymers (A-8) have low impact resistance and are prone to forming sink marks during molding. The gloss of these resin compositions is also poor. The fluidity of maleimide heat resisters is low. Maleimide heat resisters do not contain αMSt components, so they have poor compatibility with styrene resins (B-1) to (B-4). The resin compositions of Comparative Examples 4, 9, 14 and 19 containing maleimide heat resisters have low impact resistance, low surface hardness, and are prone to forming sink marks during molding. The gloss of these resin compositions is also poor. Comparative Examples 5, 10, 15 and 20 that do not contain the methacrylic copolymers of the present invention have low heat resistance, surface hardness and gloss. In any of the above characteristics, the comparative examples are inferior to the present invention.
Claims
1. A resin composition comprising: 5 to 49 parts by mass of a methacrylic copolymer (A), the methacrylic copolymer (A) comprising 5 to 97% by mass of methyl methacrylate units, 1 to 70% by mass of a structural unit (R) represented by the following formula (I), 1 to 48% by mass of an α-methylstyrene unit, 1 to 48% by mass of at least one unit selected from the group consisting of a styrene unit and a maleic anhydride unit, and 0 to 20% by mass of an unsubstituted or N-substituted maleimide unit; 51 to 95 parts by mass of one or more styrene resins (B) selected from the group consisting of ABS resins, AES resins, ASA resins and AS resins; and 0 to 30 parts by mass of a methacrylic resin (C), Wherein in formula (I), R 1 are each independently a hydrogen atom or a methyl group, R 2 is a hydrogen atom, C1-C 18 Alkyl, C3-C 12 Cycloalkyl, or C6-C 15 Organic group.
2. The resin composition according to claim 1, wherein in the methacrylic copolymer (A), The total content of the α-methylstyrene unit and the styrene unit is 2 to 40% by mass based on all structural units, and The ratio of the α-methylstyrene unit is 51 to 99% by mass based on the total content of the α-methylstyrene unit and the styrene unit. 3 . The resin composition according to claim 1 , wherein in the methacrylic copolymer (A), the content of the structural unit (R) is 20 to 60% by mass based on all structural units.
4. The resin composition according to claim 1, wherein in the methacrylic copolymer (A), the formation reaction of the structural unit (R) is an imide cyclization reaction in which an imidizing agent is added to a precursor polymer in an extruder and the resulting mixture is kneaded and reacted.
5. The resin composition according to claim 1, wherein The resin composition has a Vicat softening temperature of 105° C. to 140° C. as measured by the method described in JIS K 7206 B50 method. The resin composition according to claim 1 , wherein the styrene resin is an ASA resin. 7 . A molded body comprising the resin composition according to claim 1 .
8. An injection molded article comprising the resin composition according to claim 1. 9 . The molded article according to claim 7 , which is used as an interior part or an exterior part of an automobile.
Citation Information
Patent Citations
Magnetic recording medium
JP1986026924A
Production and use of clear heat-resistant resin
JP2000230016A
Method of manufacturing for transparent heat resistant resin and use of the same
JP2001151814A
Transparent heat resistant resin and its manufacturing method
JP2001233919A
Continuous production method for imide group containing copolymer
JP2001329021A
Cited By
Composite material and preparation method thereof
CN119798903A